Analisa Rasio Keuangan terhadap Kinerja Bank Umum di Indonesia - Hutagalung, Esther Novelina; Ratnawati, Kusuma; Djumahir (Jurnal Aplikasi Manajemen, 2013)
The bank conditions in Indonesia after the financial crisis pushed the parties involved to conductan assessment of the performance of the bank. Financial ratio analysis can help businesses, governmentsand other users of financial statements in assessing the financial condition and the bank performance. Thepurpose of this study was to analyze the effect of the Capital Adequacy Ratio (CAR), Non Performing Loan(NPL), Net Interest Margin (NIM), Operating Expenses to Operating Income, and Loan Deposit Ratio(LDR) on the bank performance is proxied by Return on Assets (ROA). The object of research is 10 (ten)largest banks in Indonesia in assets listed on the Bank Indonesia for the period 2007-2011. The method ofanalysis used is multiple regression analysis. The results showed that the variables NPL, NIM and ROAsignificant effect on ROA, while the variable CAR and LDR insignificant effect on ROA. It is clear that thebanking system at the time had good profitability, the quality of productive assets (NPL) are well preserved,NIM is quite high, the level of efficiency (ROA) is good, disbursement of funds in the form of loans not yeteffective LDR has no significant effect on ROA. The commercial banks at that time did not make optimal useof the whole potential capital, but because of the level of capital adequacy can be said to be high, then theCAR insignificant effect on ROA.